ANALISIS KOMPARASI PERSEPSI KONSUMEN TERKAIT HARGA, KUALITAS PRODUK DAN KEMASAN DALAM KEPUTUSAN PEMBELIAN TEH SYAHI HALEEB DAN TEH SUSU ALADDIN - Istighfar, Angga; Kodrat, David Sukardi (PERFORMA, 2022)
Syahi Haleeb is a business that runs in food and beverage with instant beverage product that consists of tea, milk, spices (wood, cardamom) in powder form ingredients in which then is packaged with sachets. The purpose of this research is to do comparative analysis of consumer perception related to price, product quality and packaging in purchase decision of Syahi Haleeb and Aladdin Milk Tea products. The research approach that is used is comparative research. The sample is calculated with Yamane pattern with error rate of 0.1. Based on the calculation result, the number of samples that is used is 128 people, consist of 57 people from Syahi Haleeb consumers, and 71 people of Aladdin Milk Tea consumers. The measurement scale that is used is five Likert scale. The data is collected through the distribution of online questionnaires through google form link that is given to the target respondents through whatsapp and at several cafes and restaurants around the tomb area of Sunan Ampel. Analysis and hypothesis test use validity and reliability, descriptive analysis, and MANOVA analysis. The results show that the first hypothesis (H1) There is significant difference from consumer perception related to price in purchase decision of Syahi Haleeb product and Aladdin Milk Tea is accepted. The second hypothesis (H2) There is significant difference from consumer perception related to product quality in purchase decision of Syahi Haleeb product and Aladdin Milk Tea is accepted. The third hypothesis (H3) There is significant difference from consumer perception related to packaging in purchase decision of Syahi Haleeb product and Aladdin Milk Tea product is accepted. Finally, the researcher gives managerial implication for the company to maintain the price that is offered, do product bundling by determining cheaper price, and doing special packaging design for big day commemoration in Indonesia as well as promotion of company support for Indonesia.